2014
DOI: 10.3109/09537104.2013.870333
|View full text |Cite
|
Sign up to set email alerts
|

Dental procedures in 24 patients with chronic immune thrombocytopenia in prospective clinical studies of eltrombopag

Abstract: Primary immune thrombocytopenia (ITP) is an autoimmune disease characterized by chronically low peripheral blood platelet counts. Eltrombopag is an oral, non-peptide, thrombopoietin-receptor agonist that increases platelet production. This report examines peri-procedural platelet counts and bleeding complications among chronic ITP patients requiring dental procedures while participating in clinical studies with eltrombopag. A total of 494 patients participated in five clinical studies of eltrombopag in chronic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 17 publications
0
16
0
Order By: Relevance
“…The earlier use of eltrombopag in the treatment paradigm is important for several reasons: prevention of side effects associated with therapies often used before the availability of THPO agonists, avoiding inconvenience for patients with regard to day case admission for IVIg, avoiding unnecessary exposure to blood products and reduced immunosuppression. Beyond using eltrombopag in severe, chronic and/or refractory ITP, there is growing awareness of its role in temporarily boosting the platelet count prior to surgery or other intervention, such as dental procedures (Tarantino et al , , ; Zaja et al , ). Our bridging group had a higher baseline platelet count than that of the severe ITP group, but demonstrated a higher CR rate to that already published (Zaja et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…The earlier use of eltrombopag in the treatment paradigm is important for several reasons: prevention of side effects associated with therapies often used before the availability of THPO agonists, avoiding inconvenience for patients with regard to day case admission for IVIg, avoiding unnecessary exposure to blood products and reduced immunosuppression. Beyond using eltrombopag in severe, chronic and/or refractory ITP, there is growing awareness of its role in temporarily boosting the platelet count prior to surgery or other intervention, such as dental procedures (Tarantino et al , , ; Zaja et al , ). Our bridging group had a higher baseline platelet count than that of the severe ITP group, but demonstrated a higher CR rate to that already published (Zaja et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…In two studies, not all patients with haematological malignancy were thrombocytopenic at time of extraction (Overholser, Peterson, Bergman, & Williams, 1982;Raut, Huryn, Hwang, & Zlotolow, 2001); however, for all other studies, we only included thrombocytopenic patients with platelet count < 100,000 at time of extraction. Two studies did not include the exact number of teeth extracted (Raut et al, 2001;Tarantino, Fogarty, Shah, & Brainsky, 2015). No bleeding complications were reported among the ITP patients, and 11 patients (5.5%) with thrombocytopenia related to haematological malignancy or disease had bleeding (7 minor and 4 moderate bleeding episodes) ( Table 2 presents details of platelet transfusions and bleeding episodes.…”
Section: Patients Procedures and Complicationsmentioning
confidence: 99%
“…An even lower threshold (platelet count < 30,000/μl) was allowed for scaling and root planing (Morimoto, Niwa, Imai, & Kirita, 2004). In two studies, the decision on platelet transfusion threshold was based on the attending specialist judgement (Raut et al, 2001;Tarantino et al, 2015).…”
mentioning
confidence: 99%
“…1 Another 2015 study of 24 patients with immune thrombocytopenia showed no bleeding complications as long as severely thrombocytopenic patients were given supplemental platelet transfusion preoperatively. 2 The most relevant article has been chosen for critical appraisal. The 2013 Mayo Clinic study explicitly addresses safety and complications of tooth extraction in thrombocytopenic patients without a focus on a particular disease.…”
Section: -2mentioning
confidence: 99%